Effect of molybdenum and tungsten on the reduction of nitrate in nitrate reductase, a DFT study - Habib, Uzma; Hofmann, Matthias (Chemistry central journal, 2017)
The molybdenum and tungsten active site model complexes, derived from the protein X-ray crystal structure of the first W-containing nitrate reductase isolated from Pyrobaculum aerophilum, were computed for nitrate reduction at the COSMO-B3LYP/SDDp//B3LYP/Lanl2DZ(p) energy level of density functional theory. The molybdenum containing active site model complex (Mo-Nar) has the largest activation energy (34.4 kcal/mol) for the oxygen atom transfer from the nitrate to the metal center as compared to the tungsten containing active site model complex (W-Nar) (12.0 kcal/mol). Oxidation of the educt complex is close to thermoneutral (-1.9 kcal/mol) for the Mo active site model complex but strongly exothermic (-34.7 kcal/mol) for the W containing active site model complex, however, the MVI to MIV reduction requires equal amount of reductive power for both metal complexes, Mo-Nar or W-Nar.